What makes wildlife wild? How identity may shape the public trust versus wildlife privatization debate - Markus J. Peterson; M. Nils Peterson; Tarla Rai Peterson (Wildlife Society Bulletin)
ABSTRACT Wildlife conservation policy discussions in the United States and Canada often revolve around historical accounts of the success of wildlife management grounded in the public trust doctrine. We suggest that the usefulness of these discussions is partially limited by failure to consider the importance of wildlife “identity” rooted in freedom (i.e., how humans socially construct the “wildness” dimension of wild animals). To demonstrate the interrelations between identity and freedom, we explain that the class of subjects people care most about—partners, children, and people in general—typically should not be privately owned (i.e., chattel) because freedom (as opposed to slavery) is generally accepted as central to human identity, and its abrogation therefore degrades human identity. The degree to which this ethical argument applies to privatization of wildlife depends upon the relationship between freedom and the identity of wildlife as perceived by society. Thus, we suggest policy decisions regarding privatization of wildlife will be more accurately deliberated if society and wildlife professionals more completely considered the degree to which freedom is essential to a wild species’ identity and the degree to which that identity is inviolable. © 2016 The Wildlife Society.